The Making of Land Deed and the Registration of Land Rights Transition through the Inheritance by the Village Community and its Legal Implications (A Study in Sub District of Lingsar, the District of East Lombok) - Arba Arba; Sahnan Sahnan (Faculty of Law, University of Mataram, 2020)
The aims of this research are to review and analyzing the society behavior in making of the land deed and the registration of land transition on the transfer of rights through inheritance, and its legal implications if the transfer of the land rights without the land deed and was not registered in the national land agency. The study of this research is empirical legal studies and using the normative approach as well the sociolegal approach. Which are the library conduct and the data from the field, the result of this research reviewed and analyzed in the normative and qualitative ways.The normative analysis using the legal interpretation while the qualitative analysis using the data reviews. Further, it is concluded through the deductive reasoning and the result of this research after reviewed and analyzed are as follows: 1. the reason of the society in sub district of Lingsar tend to not make the land deed and did not do the registration in the national land agency on the matters of transfer of land rights are : the heritance custom, the legal tradition of the society have been rooted, the registration needs a lot of money to spend, and the procedures of land deed making and its registration takes a long period of time. 2. The legal implication of land rights through inheritance which was not registered and the deed was not made is legitimate and is protected under the law, since the heritance is the legal event which according to the law where the rights of inheritance land is transferred, the making of deed and registration only as the administration obligations.